2010
DOI: 10.1159/000314853
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Heparin-Binding Protein in Bacterial Infections

Abstract: Infectious diseases remain a major health problem, where sepsis and other severe infectious diseases are common causes of morbidity and mortality. The importance of early and appropriate treatment of sepsis and severe bacterial infections has been underlined by the successes of measures like the Surviving Sepsis Campaign, among others. Thus, there is a need for clinical and laboratory tools to identify a patient with severe infection early and to distinguish between bacterial and non-bacterial conditions. Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 85 publications
1
74
0
Order By: Relevance
“…HBP is a cytokine released from activated neutrophils by bacterial stimulation of β 2 -integrins ligation [10]. Our results are consistent with the previous findings by Kjolvmark et al that UHBP levels of >32 ng/mL are the optimal cutoff for UTI Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…HBP is a cytokine released from activated neutrophils by bacterial stimulation of β 2 -integrins ligation [10]. Our results are consistent with the previous findings by Kjolvmark et al that UHBP levels of >32 ng/mL are the optimal cutoff for UTI Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Various bacterial infections, including APN and urosepsis, stimulate the release of HBP into the systemic circulation [10,3]. A recent study showed that urine HBP (UHBP) provided better sensitivity and specificity compared to urine dipstick analysis in children with upper or lower urinary tract infection (UTI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, antibodies which are found in TRALI have been shown to trigger discharge of azurocidin from neutrophils (192). In addition, in circumstances that may lead to ALI such as severe burns or sepsis, circulating azurocidin levels are increased significantly, allowing speculation on their potential role in lung damage (193)(194)(195).…”
Section: Neutrophil-derived Cationic Polypeptidesmentioning
confidence: 99%
“…In addition, patients with severe infection typically suffer from acute lung injury resulting in increased pulmonary microvascular leakage [10]. This is also associated with an increase in plasma levels of heparinbinding protein (HBP; also called azurocidin or CAP37), a granule-associated protein secreted by polymorphonuclear leukocytes (PMNs), and an increase in the risk of bacteraemia [11][12][13][14]. Furthermore, IAV infection elicits a thrombotic inflammatory response, which increases the abundance of fibrinogen (Fg)/fibrin and fibronectin (Fn) in the lung [15].…”
Section: Introductionmentioning
confidence: 99%